Hi all

Ran into a problem on a quiz that for the life of me I thought I was solving correctly but the proof wasnt working.

Anyhow the question was

Prove that

Fxx + Fyy = 0

F(x,y) = LN(SQRT(X^2+Y^2))

My solution

Property of logs converted my problem to

1/2 LN(X^2+Y^2)

Derived with respect to X = Fx (x,y) = x/(x^2+y^2)

Derived with respect to Y = Fy (x,y) = y/(x^2+y^2)

Derived Fx with respect to X = Using the power rule for the function (x(x^2+y^2)^-1)

= (1)(x^2+y^2)^-1) + (x)(2x)(-1)(x^2+y^2)^-2)

=1/(x^2+y^2) - 2x^3/(x^2+y^2)^2)

So Fxx = 1/(x^2+y^2) - 2x^3/(x^2+y^2)^2)

Derived Fy with respect to y = Using the power rule for the function (y(x^2+y^2)^-1)

= (1)(x^2+y^2)^-1) + (y)(2y)(-1)(x^2+y^2)^-2)

=1/(x^2+y^2) - 2y^3/(x^2+y^2)^2)

So Fyy = =1/(x^2+y^2) - 2y^3/(x^2+y^2)^2)

If I do Fxx + Fyy I dont think I get 0.

Any suggestions on where I went wrong please!

Thanks